Divdabju lietojums latviešu un lietuviešu literāros tekstos - Rūķe-Draviņa, Velta (Baltistica, 1989)
PARTICIPLES AS A STYLISTIC FEATURE IN LATVIAN AND LITHUANIAN LITERARY TEXTS The present article is a contrastive analysis of the usage and frequency of Latvian and Lithuanian participles in modern prose. By comparing the inventory of participles in both languages we notice that the variety of participial formations in Lithuanian is greater than in Latvian. Syntactic models containing participles and the frequency of participles in a present-day text also differ. The syntactic synonymy allows the native speaker to choose between two or three alternatives (with or without participles) but the choice depends both on the structure of the Lithuanian/Latvian language and on the individual personality who prefers some special syntactic model. The numerical data for the frequency of occurrence of participial forms (based on novels and short stories of six contemporary Latvian writers and analysed by Aleksandra Eiche in her doctoral thesis) showed the same total number of forms in all prose works but individual differences in the frequency of participles in -ošs, -dams and -ot. In order to compare the frequency of participles in Lithuanian and Latvian modern prose, two Lithuanian novels (Alkana žemė by V. Bubnys and Sakmė apie Juzą by J. Baltušis) and Kalpa zēna vasara by the Latvian author J. Akurāters were chosen for an analysis in detail. These original texts were compared with their translations into Latvian/Lithuanian. The comparison shows that the total number of participles used in the current text is somewhat greater in Latvian prose (depending on the frequent use of compound tenses) but that the difference lies in the relative frequency of special types: the usage of -is and -ts dominate in Latvian prose whereas Lithuanian authors use the present participles in -ąs more often than the Latvian writers choose the corresponding forms in -ošs.